Recommendations for Control and Mitigation of Laurel Wilt and Ambrosia Beetle Vectors in Commercial Avocado Groves in Florida - Jonathan Henry Crane; Daniel Carrillo; Edward A. Evans; Romina Gazis; Bruce A Schaffer; Fredy H Ballen Orozco; Jeff Wasielewski (EDIS, 2020)
The lethal laurel wilt epidemic affecting avocado trees in Florida is caused by a fungal pathogen-ambrosia beetle complex (LW-AB). The death of over 120,000 commercial avocado trees in Florida may be attributed to LW-AB. Recommendations for control and mitigation of this epidemic are needed to guide commercial producers in their decision-making process. This new 8-page publication of the UF/IFAS Horticultural Sciences Department outlines the LW-AB epidemic, provides information on the pathogen and ambrosia beetle vectors, provides a brief outline of current research findings, and offers recommendations for the control and mitigation of LW-AB. Written by Jonathan H. Crane, Daniel Carrillo, Edward A. Evans, Romina Gazis, Bruce Schaffer, Fredy Ballen, and Jeff Wasielewski.